1996
DOI: 10.1046/j.1365-3083.1996.d01-25.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Monocytes in the Up‐Regulation of the Early Activation Marker CD69 on B and T Murine Lymphocytes Induced by Microbial Mitogens

Abstract: CD69 is an early marker of lymphoid cell activation. The authors report on an up-regulation of CD69 in splenic B and T cells of C57Bl/6 mice after administration of lipopolysaccharide (LPS) or microbial immunosuppressive/mitogenic (ISM) proteins produced by C. albicans (p43) and African Swine Fever Virus (p36). This up-regulation of CD69 was observed 6 and 24 h after mitogenic treatments. The same pattern of increased CD69 expression was observed in the lymph nodes of mice treated with p43 or LPS, whereas p36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
6
26
1
Order By: Relevance
“…(iii) Although activated CD4 ϩ T cells expressed similar levels of TLR4 and TLR2, the cells did not respond to LPS, a recognized ligand for TLR4 (33). This is consistent with a large number of reports in the literature (34)(35)(36). LPS has recently been reported to activate CD4 ϩ CD25 ϩ T cells in mice (32).…”
Section: Tlr Messages Have Been Reported To Be Present In T Cells (26supporting
confidence: 88%
“…(iii) Although activated CD4 ϩ T cells expressed similar levels of TLR4 and TLR2, the cells did not respond to LPS, a recognized ligand for TLR4 (33). This is consistent with a large number of reports in the literature (34)(35)(36). LPS has recently been reported to activate CD4 ϩ CD25 ϩ T cells in mice (32).…”
Section: Tlr Messages Have Been Reported To Be Present In T Cells (26supporting
confidence: 88%
“…Such a rapid high expression of CD69 has been described in other models of virus infection in which viral antigens from either mouse mammary tumor virus, rhinovirus, or African swine fever virus induced high CD69 expression among various lymphocyte populations (8,39,42).…”
Section: Discussionmentioning
confidence: 71%
“…Other studies of virus-induced nonspecific cell activation have suggested that macrophages or monocytes induce this nonspecific expression of CD69 via the secretion of soluble factors in situ (8,39). VEEV E2 expression seemed to be restricted to the splenic macrophage population in both untreated and PEG IFN-␣-treated mice.…”
Section: Discussionmentioning
confidence: 92%
“…These data suggest that CD8 + iNKT cells probably have a more Th1-skewed phenotype than conventional CD8 -iNKT cells. Secondly, we examined the activation status of NKT cells by measuring CD69 on NKT cells upon α-GalCer stimulation, since it was previously reported that α-GalCer stimulation of NKT cells leads to significant up-regulation of CD69 on NKT cells (Testi et al, 1994;Vilanova et al, 1996). CD8 + iNKT cells up-regulated CD69 as much as CD8 -iNKT cells upon α-GalCer stimulation, suggesting that CD8 + iNKT cells have the same activation potency as CD8 -iNKT cells ( Figure 3B).…”
Section: Th1-skewed Response Of Cd8 + Inkt Cells Against α-Galcermentioning
confidence: 99%